2020
DOI: 10.1007/s10340-020-01266-y
|View full text |Cite
|
Sign up to set email alerts
|

Yeast species affects feeding and fitness of Drosophila suzukii adults

Abstract: Yeasts play an important role in the life cycle and biology of the insect pest Drosophila suzukii (Matsumura), commonly known as the spotted wing drosophila (SWD). Adult and larvae of this species are known to feed and benefit from yeast in their diet. In addition, yeasts were found to be attractive to SWD and were repeatedly found to be associated with SWD. Among those, Hanseniaspora uvarum is the most commonly mentioned. The present study explores the chemical composition and the effects of three H. uvarum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 80 publications
1
42
0
1
Order By: Relevance
“…In this study, a broad qualitative approach was used including a wide range of non-polar compounds. Considering that the same yeast species and microorganisms were grown and collected under the same conditions reported in the paper by Spitaler et al [ 52 ], the results of this work represent an implementation of the above-mentioned study and may support future entomological studies.…”
Section: Resultsmentioning
confidence: 65%
See 4 more Smart Citations
“…In this study, a broad qualitative approach was used including a wide range of non-polar compounds. Considering that the same yeast species and microorganisms were grown and collected under the same conditions reported in the paper by Spitaler et al [ 52 ], the results of this work represent an implementation of the above-mentioned study and may support future entomological studies.…”
Section: Resultsmentioning
confidence: 65%
“…The yeast H. uvarum has been found to be more attractive for SWD flies compared to other Drosophila -associated yeasts, including S. cerevisiae and I. terricola , when offered in a choice test [ 19 ]. In addition, Lewis and Hamby [ 7 ] demonstrated that larvae of SWD prefer to feed on H. uvarum compared to S. cerevisiae and I. terricola , while Spitaler et al [ 52 ] showed that SWD adults benefit from H. uvarum and S. vini in their diet compared to other species, including S. cerevisiae . In this study, H. uvarum and S. cerevisiae were found to have a similar global lipid profile.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations